PENGEMBANGAN BUKU CERITA FABEL PADA SISWA SEKOLAH DASAR - Husain, Fauzia Putri Meylan; Husain, Rusmin; Pulukadang, Wiwy Triyanty; Monoarfa, Fidyawati; Husain, Rustam I (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT Focus of the problem in this study is how to define learning using fable story books for second-grade students at SDN 7 Limboto Barat, Gorontalo Regency and how to design, develop, and disseminate fable story books. The purpose of this study is to describe the definition of learning using fable story books for second-grade students at SDN 7 Limboto Barat, Gorontalo Regency, to design, develop, and disseminate fable story books. The method used is the development research method using the Thiagarajan (1974) model design, namely the 4D model consisting of 4 stages, namely definition, design, development, and dissemination. The results of the fable story book development research based on media expert validation obtained a percentage of 90% (very feasible), language expert validation obtained a percentage of 84% (very feasible), practitioner expert validation in terms of language obtained a percentage of 98% (very feasible) and practitioner expert validation in terms of media obtained a percentage of 96% (very feasible). The results of this validation obtained an average percentage of 92% (very feasible). Based on the research results, it can be concluded that the development of fable story books is very suitable for use in the learning process. ABSTRAK Fokus masalah dalam penelitian ini adalah bagaimana pendefinisian pembelajaran dengan menggunakan buku cerita fabel pada siswa kelas II di SDN 7 Limboto Barat Kabupaten Gorontalo dan bagaimana merancang, mengembangkan, dan menyebarkan buku cerita fabel. Tujuan penelitian ini adalah mendeskripsikan pendefinisian pembelajaran dengan menggunakan buku cerita fabel pada siswa kelas II di SDN 7 Limboto Barat Kabupaten Gorontalo, merancang, mengembangkan, dan menyebarkan buku cerita fabel. Metode yang digunakan adalah metode penelitian pengembangan yang menggunakan desain model Thiagarajan (1974), yaitu model 4D yang terdiri dari 4 tahap, yaitu pendefinisian, perancangan, pengembangan, dan penyebaran. Hasil penelitian pengembangan buku cerita fabel berdasarkan validasi ahli media memperoleh persentase 90% (sangat layak), validasi ahli bahasa memperoleh persentase 84% (sangat layak), validasi ahli praktisi dari segi bahasa memperoleh persentase 98% (sangat layak) dan validasi ahli praktisi dari segi media memperoleh persentase 96% (sangat layak). Hasil validasi ini memperoleh persentase rata-rata 92% (sangat layak). Berdasarkan hasil penelitian, dapat disimpulkan bahwa pengembangan buku cerita fabel sangat layak untuk digunakan dalam proses pembelajaran.